ANALISIS KEBUTUHAN MEDIA INTERAKTIF DALAM PEMBELAJARAN PLBJ PADA SISWA KELAS IV SD - Fauziyyah Salsabila, Relia; Indah Wardatussa’idah; Chrisnaji Banindra Yudha (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Environmental and Cultural Education Jakarta is a local content subject specialized in schools in the Jakarta area. The assumption that PLBJ is a local content and not a core subject causes a lack of attention from teachers & schools to the achievement of this subject. One form of this is the lack of use of interactive learning media in PLBJ learning process at SDN Karet 04 Pagi. This study aims to identify the extent to which interactive learning media is needed in PLBJ Learning MaterialHistorical Tourist Attractions in Jakarta. The research subjects were teachers and fourth grade students of SDN Karet 04 Pagi. The research method used a qualitative method with a descriptive approach. The results showed that both teachers and grade IV students need interactive media in PLBJ Learning.